A Role Of Well-Being In Mediating Relationship Between Work Commitment And Religious Teacher's Performance - Najmudin, Najmudin; Syihabudin, Syihabudin; Ma'zumi, Ma'zumi; Suja'i, Suja'i; Jakaria, Jakaria; Najib, Mohamad Ainun (FEB Universitas Sultan Ageng Tirtayasa, 2024)
This research aims to determine the direct and indirect relationships between the variables of work commitment and the performance of Islamic boarding school religious teachers in Serang Regency, Banten Province. (1) Does work commitment significantly influence the performance of modern Islamic boarding school religious teachers in Serang Regency, Banten Province? (2) Does work commitment significantly influence the well-being of modern Islamic boarding school religious teachers in Serang Regency, Banten Province? (3) Does well-being have a significant positive influence on the performance of modern Islamic boarding school religious teachers in Serang Regency, Banten Province? (4) Does work commitment, through well-being, have a significant positive influence on the performance of modern Islamic boarding school religious teachers in Serang Regency? The population of this study consists of all modern Islamic boarding school religious teachers in Serang Regency, Banten Province. The sample size is 84 individuals, obtained by multiplying the total number of indicators by 7, according to Ferdinand's theory. Data collection was done by distributing questionnaires via Google Forms. The data were processed using Smart PLS software version 3.2.9 and analyzed using path analysis. The results of this study indicate that (1) Work commitment has a significant positive influence on the performance of modern Islamic boarding school religious teachers in Serang Regency, Banten Province. (2) Work commitment has a significant positive influence on the well-being of modern Islamic boarding school religious teachers in Serang Regency, Banten Province. (3) Well-being has a significant positive influence on the performance of modern Islamic boarding school religious teachers in Serang Regency, Banten Province. (4) Work commitment, through well-being, has a significant positive influence on the performance of modern Islamic boarding school religious teachers in Serang Regency.